Answer
$x=\pm\dfrac{\sqrt{6}}{3}$
Work Step by Step
Using the properties of equality, the given equation, $
3x^2-2=0
,$ is equivalent to
\begin{array}{l}\require{cancel}
3x^2=2
\\\\
x^2=\dfrac{2}{3}
.\end{array}
Taking the square root of both sides, then the solutions of the given equation are
\begin{array}{l}\require{cancel}
x=\pm\sqrt{\dfrac{2}{3}}
\\\\
x=\pm\sqrt{\dfrac{2}{3}\cdot\dfrac{3}{3}}
\\\\
x=\pm\sqrt{\dfrac{6}{(3)^2}}
\\\\
x=\pm\dfrac{\sqrt{6}}{\sqrt{(3)^2}}
\\\\
x=\pm\dfrac{\sqrt{6}}{3}
.\end{array}